Improving the Use of Computer-Based Information Resources within the Engineering Classroom - Kerr, Michael E.; Holloway, William H. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1977)
An instructional development project at the University of Kansas focused upon two major objectives: (1) to develop teaching strategies to introduce engineering students and faculty to literature searching on computerized data bases, and (2) to help students develop effective on-line search strategies. A faculty workshop and an undergraduate engineering course designed to teach students methods of retrieving relevant literature were used for reaching the objectives. Attitude questionnaires and performance evaluations indicated that student attitudes toward on-line computer search methods, as well as quantity of relevant literature found, improved with the instruction and subsequent use of on-line search methods. (CMV)
Sponsoring Agency: National Science Foundation, Washington, DC. Div. of Science Information.
Contract Number: DSI 77-23193.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Course Content; Course Evaluation; Curriculum Development; Databases; Engineering Education; Higher Education; Information Retrieval; Instructional Innovation; Online Systems; Relevance (Information Retrieval); Search Strategies; Student Attitudes; Reports, Research